Monitoring in clinical trials of complementary and alternative medicine (2020)
Background Clinical trial monitoring is an essential activity for quality assurance (QA) to ensure the protection of human rights and the reliability and transparency of the data collection process. The purpose of this article is to enhance the understanding of monitoring process and major findings in clinical trials of complementary and alternative medicine (CAM). Methods Based on International Conference on Harmonization of technical requirements for registration of pharmaceuticals for human use (ICH-GCP), we summarized main concept of monitoring process. Personal experiences on monitoring for CAM studies were also narratively described. Results In this brief article, the basic concept of QA and quality control (QC), various monitoring activities during the study process, and major findings regarding clinical trials of CAM are suggested in an effort to improve understanding of monitoring in clinical research on CAM. Conclusion When performing clinical trials for CAM-related interventions, the monitoring recommended in GCP is needed to be recognized as a mandatory element in the course of CAM research.